Implementation guide for IBM Spectrum Virtualize for public cloud on Microsoft Azure version 8.4.3 - Greenfield, Andrew; Shea, Jackson; Kratt, Katja; Dill, Lars; Torolho, Leandro; Olsson, Nils; Deshpande, Pankaj; Sharma, Sushil; Gucer, Vasfi (IBM Redbooks, 2022)
IBM® Spectrum Virtualize for Public Cloud is now available on Microsoft Azure. With IBM Spectrum® Virtualize for Public Cloud 8.4.3, users can deploy a highly available two-node cluster running IBM Spectrum Virtualize for Public Cloud on supported Microsoft Azure virtual machines (VMs). This all-inclusive, bring your own license (BYOL) software offering provides the ability to virtualize, optimize, and provision supported Azure Managed Disk to applications that require the performance of block storage in the cloud with the added efficiencies that IBM Spectrum Virtualize for Public Cloud brings to native infrastructure as a service (IaaS) that is provided by Microsoft Azure. This IBM Redbooks publication gives a broad understanding of the IBM Spectrum Virtualize for Public Cloud on Azure architecture. It also provides planning and implementation details of the common use cases for this new product. This book helps storage and networking administrators plan, implement, install, and configure the IBM Spectrum Virtualize for Public Cloud on Azure offering. It also provides valuable troubleshooting tips.
Keywords: Database management -- Computer programs; Information storage and retrieval systems; Cloud computing; Database Management Systems; Information Systems; Bases de données; Gestion; Logiciels; Systèmes d'information; Infonuagique; Database management; Computer programs